2020
DOI: 10.26434/chemrxiv.12480152.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermo-Responsive Wettability via Surface Roughness Change on Polymer-Coated Titanate Nanorod Brushes Toward Fast and Multi-Directional Droplet Transport

Abstract: A novel approach for thermo-responsive wettability has been accomplished by surface roughness change induced by thermal expansion of paraffin coated on titanate nanostructures. The surface exhibits thermo-responsive and reversible wettability change in a hydrophobic regime; the surface shows superhydrophobicity with contact angles of ~157° below 50 °C and ~118° above 50 °C due to a decrease of surface roughness caused by thermally-expanded paraffin at higher temperatures. Reversible wettability change of ~40° … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Light fields, electric fields and magnetic fields, as well as other external stimuli such as thermal fields, 34,78,107,122 pH value gradients 33,123 and mechanical vibrations 111 have been used to manipulate droplets. Banuprasad et al 124 reported on a method for rapid droplet transport over a poly (N-isopropyl acrylamide) (ii) droplet carrying on climbing movement on the bridge-like magnetic droplet microfluidic platform (MDMP), under the control of magnetic probe.…”
Section: Droplet Manipulation Strategies Under Other External Stimulimentioning
confidence: 99%
“…Light fields, electric fields and magnetic fields, as well as other external stimuli such as thermal fields, 34,78,107,122 pH value gradients 33,123 and mechanical vibrations 111 have been used to manipulate droplets. Banuprasad et al 124 reported on a method for rapid droplet transport over a poly (N-isopropyl acrylamide) (ii) droplet carrying on climbing movement on the bridge-like magnetic droplet microfluidic platform (MDMP), under the control of magnetic probe.…”
Section: Droplet Manipulation Strategies Under Other External Stimulimentioning
confidence: 99%